Influenza Vaccine Effectiveness in the United States During 2012–2013: Variable Protection by Age and Virus Type. (18th November 2014) - McLean, Huong Q.; Thompson, Mark G.; Sundaram, Maria E.; Kieke, Burney A.; Gaglani, Manjusha; Murthy, Kempapura; Piedra, Pedro A.; Zimmerman, Richard K.; Nowalk, Mary Patricia; Raviotta, Jonathan M.; Jackson, Michael L.; Jackson, Lisa; et al.
Abstract: Background. During the 2012–2013 influenza season, there was cocirculation of influenza A(H3N2) and 2 influenza B lineage viruses in the United States. Methods. Patients with acute cough illness for ≤7 days were prospectively enrolled and had swab samples obtained at outpatient clinics in 5 states. Influenza vaccination dates were confirmed by medical records. The vaccine effectiveness (VE) was estimated as [100% × (1 − adjusted odds ratio)] for vaccination in cases versus test-negative controls. Results. Influenza was detected in 2307 of 6452 patients (36%); 1292 (56%) had influenza A(H3N2), 582 (25%) had influenza B/Yamagata, and 303 (13%) had influenza B/Victoria. VE was 49% (95% confidence interval [CI], 43%–55%) overall, 39% (95% CI, 29%–47%) against influenza A(H3N2), 66% (95% CI, 58%–73%) against influenza B/Yamagata (vaccine lineage), and 51% (95% CI, 36%–63%) against influenza B/Victoria. VE against influenza A(H3N2) was highest among persons aged 50–64 years (52%; 95% CI, 33%–65%) and persons aged 6 months–8 years (51%; 95% CI, 32%–64%) and lowest among persons aged ≥65 years (11%; 95% CI, −41% to 43%). In younger age groups, there was evidence of residual protection from receipt of the 2011–2012 vaccine 1 year earlier. Conclusions. The 2012–2013 vaccines were moderately effective in most age groups. Cross-lineage protection and residual effects from prior vaccination were observed and warrant further investigation.